2015
DOI: 10.1371/journal.pntd.0004128
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Lutzomyia verrucarum and Lutzomyia longipalpis Sand Flies (Diptera: Psychodidae) by Bartonella bacilliformis, the Etiologic Agent of Carrión’s Disease

Abstract: Bartonella bacilliformis is a pathogenic bacterium transmitted to humans presumably by bites of phlebotomine sand flies, infection with which results in a bi-phasic syndrome termed Carrión’s disease. After constructing a low-passage GFP-labeled strain of B. bacilliformis, we artificially infected Lutzomyia verrucarum and L. longipalpis populations, and subsequently monitored colonization of sand flies by fluorescence microscopy. Initially, colonization of the two fly species was indistinguishable, with bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 23 publications
0
38
0
1
Order By: Relevance
“…The genus Bartonella encompasses more than 33 species of Gram-negative, facultative intracellular and hemotropic bacteria, which can cause chronic intraerythrocytic infections in their mammalian hosts, especially rodents and humans (Chomel et al 2009). Several blood-feeding arthropods are involved in the transmission of these bacteria, such as fleas, sand flies, sucking lice, Acari, and other arthropods (Kosoy et al 2012, Kamani et al 2013, Battisti et al 2015, Regier et al 2016.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Bartonella encompasses more than 33 species of Gram-negative, facultative intracellular and hemotropic bacteria, which can cause chronic intraerythrocytic infections in their mammalian hosts, especially rodents and humans (Chomel et al 2009). Several blood-feeding arthropods are involved in the transmission of these bacteria, such as fleas, sand flies, sucking lice, Acari, and other arthropods (Kosoy et al 2012, Kamani et al 2013, Battisti et al 2015, Regier et al 2016.…”
mentioning
confidence: 99%
“…We cannot confirm whether sand flies are vectors of this bacterium in this area, since the arthropod could feed on blood meal from an infected host and not necessarily transmit the microorganism. It is possible that other lineages of Bartonella (pathogenic or nonpathogenic) can circulate in the fauna from Veracruz, yet the range of vectors involved in the transmission of Bartonella species remains to be established (Maroli et al 2013, Battisti et al 2015.…”
mentioning
confidence: 99%
“…After oviposition and the death of the insects, PCR was performed to detect the microorganism. The results showed that insects fed blood with a higher bacteremia had a shorter life, and most of the infected females (35 out of 36) were unable to perform oviposition, while no Bartonella-positive descendant of the remaining infected female was obtained, supporting the hypothesis of a higher mortality of L. verrucarum in the presence of higher bacteremia and the absence of vertical (223). Unfortunately, analysis of feces or diuretic body fluids was not carried out in the L. verrucarum group.…”
Section: Transmissionmentioning
confidence: 65%
“…Thus, L. longipalpis eliminates B. bacilliformis, while bacteria in L. verrucarum survive on blood meal digestion, colonizing the entire digestive tract of the sand fly(223). Although sporadic transmission of Carrion's disease related to L. longipalpis cannot be ruled out because the microorganism remains viable within L. longipalpis for up to 11 days, no mechanical transmission or isolation of viable B. bacilliformis has been obtained from feces or diuretic body fluids(223). B. bacilliformis was not observed in feces or diuretic body fluids of L. longipalpis or in eggs of L. verrucarum and L. longipalpis…”
mentioning
confidence: 99%
“…B. bacilliformis is transmitted between humans through the bite of female phlebotomine sand flies, specifically Lutzomyia spp. [4,5]. The endemic region of Carrión's disease has historically been limited to arid, high-altitude valleys (600 -3200m) in the Andes Mountains of Peru, Colombia, and Ecuador, reflecting the habitat of the sand fly vector [6,7].…”
Section: Introductionmentioning
confidence: 99%